2022
DOI: 10.3389/fimmu.2022.940835
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of soluble CD27, BTLA, and TIM-3 predicts the development of nosocomial infection in pediatric burn patients

Abstract: Thermal injury induces concurrent inflammatory and immune dysfunction, which is associated with adverse clinical outcomes. However, these effects in the pediatric population are less studied and there is no standard method to identify those at risk for developing infections. Our goal was to better understand immune dysfunction and identify soluble protein markers following pediatric thermal injury. Further we wanted to determine which early inflammatory, soluble, or immune function markers are most predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 74 publications
(95 reference statements)
0
24
0
Order By: Relevance
“…Measurements of immunoregulatory checkpoint proteins that regulate T cells (soluble BTLA, TIM-3, and CD27) can also indicate adaptive immune dysfunction. Some researchers have observed that soluble BTLA and TIM-3 are elevated in sepsis patients, whereas our own work has shown similar increases in patients who develop infections after burn injury (10,30,31). Soluble CD27 has been shown to inhibit T cell proliferation and has also been elevated in pediatric burn patients who later develop infections (10,32).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Measurements of immunoregulatory checkpoint proteins that regulate T cells (soluble BTLA, TIM-3, and CD27) can also indicate adaptive immune dysfunction. Some researchers have observed that soluble BTLA and TIM-3 are elevated in sepsis patients, whereas our own work has shown similar increases in patients who develop infections after burn injury (10,30,31). Soluble CD27 has been shown to inhibit T cell proliferation and has also been elevated in pediatric burn patients who later develop infections (10,32).…”
Section: Discussionmentioning
confidence: 63%
“…As such, the adaptive immune system, which is typically thought to follow the innate immune system, also plays a crucial role in determining the risk of an individual developing an infection after pediatric burn injury. Previously, our group and others have shown reductions in CD4 + lymphocytes and PHA-stimulated cytokine production (an important measurement of T cell function) within the first 72 h after burn injury (8,10,12,29). Moreover, both CD4 + lymphocytes and PHA-stimulated cytokine production are shown to be further suppressed in pediatric burn patients who develop infections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations